Assessment of type II diabetes mellitus drug therapy in diabetes clinic of a tertiary care teaching hospital in Addis Ababa - Alemseged Ayele Asfaw; Nahom Mulugeta Mamo; Abel Tesfaye Anshabo; Segewkal Hawaze (Archives of Global Professionals, 2014)
Background: Prevalence of type II diabetes mellitus(T2DM) is substantially increasing in Ethiopia but there are no studies on its drug therapy. Objective: To assess drug therapy for T2DM and check association between fasting blood glucose levels with patient demographics, clinical characteristics and medications. Materials and Methods: A cross-sectional institution based study was conducted on T2DM patients over a 1 month period using patient chart review and key informant interview at the diabetes clinic of Tikur Anbessa Specialized Hospital (TASH). Results: Of 103 patients enrolled females accounted 59.2%. The mean age was 52.2 years and 96.12% of patients were from Addis Ababa. The mean fasting blood glucose (FBG) and body mass index (BMI) were 155.99 mg/dl and 26.4 kg/m 2 respectively. About 51.45% of the patients were overweight; and neutral protamine hagedorn insuline (NPH) (56.3%), metformin plus glibenclamide (19.4%) and metformin (10.7%) were the most common drug therapies. But there was no significant association of FBG levels of patients with either, gender, age, BMI or medications. Conclusions: The drug therapy at the diabetes clinic was in line with recommendations of International Diabetes Federation (IDF)despite lack of uniform guideline.